Modelação e Análise Espacial das Condicionantes do Crime Contra o Património em Portugal Continental - Tavares, Joana Paulo (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management